Extroversion Versus Introversion, Instructional Strategies, and Reading Comprehension Performance in Multilingual EFL Classroom - Devi Hellystia (Journal of English Language Teaching and Cultural Studies, 2018)
This paper tries to investigate if there is any positive correlation between personality types (extrovert and introvert), instructional strategies (cooperative and individual learning), and the success of students’ performance in reading comprehension. This is a pilot study which was conducted in one of secondary school in Indonesia. This research employed experimental research. The subjects were forty students. The finding of this study shows that; (1) the success of students’ performance in reading comprehension which applied cooperative strategy is higher than those applied individual instruction. (2) There are no substantial differences in the success of students’ performance   be tween students who have extrovert type of personality and those who have introvert type of personality. (3) There is a positive interaction between instructional strategies and the type of personalities (extrovert and introvert)  on the success of students performance in reading comprehension. (4) The success of extrovert type students in their performance on reading comprehension which applied cooperative strategy is higher than those applied individual instruction. (5) The success of introvert type students in their performance on  reading comprehension which applied individual Instruction is higher than those applied cooperative instruction.